2010
DOI: 10.1007/s11738-010-0623-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salicylic acid and methyl jasmonate on antioxidant systems of Haematococcus pluvialis

Abstract: The influence of phytohormones, salicylic acid (SA) and methyl jasmonate (MJ) on the antioxidant systems in Haematococcus pluvialis was investigated. Both SA and MJ at 500 lM concentration reduced the growth of alga with salicylic acid, having more pronounced effect. Carotenoid and chlorophyll contents were decreased by SA and increased by MJ. Salicylic acid (100 lM) increased astaxanthin content to 6.8-fold under low light (30 lmol m -2 s -1 ), while MJ (10 lM) showed marginal increase in astaxanthin. Salicyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 31 publications
5
34
1
Order By: Relevance
“…They found that JA at high concentrations (10 -5 -10 -4 M) resulted in a decrease in cell number and photosynthetic pigments, whereas JA at low concentrations (10 -8 -10 -6 M) induced increases in both of these, which is also in accordance with our present data regarding increased lipid content under 0.5 mg/L JA induction and decreased lipid production under 10-20.0 mg/ L JA induction in Chlorella strains. Furthermore, both SA and MJ at 500 mM concentrations displayed inhibitory effects on the growth of algal cells and carotenoid and chlorophyll contents, whereas higher concentrations of SA and MJ inhibited astaxanthin accumulation in Haematococcus pluvialis (Raman and Ravi, 2011). Gao et al (2012a) also reported that JA was an effective regulator that stimulated astaxanthin production in H. pluvialis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…They found that JA at high concentrations (10 -5 -10 -4 M) resulted in a decrease in cell number and photosynthetic pigments, whereas JA at low concentrations (10 -8 -10 -6 M) induced increases in both of these, which is also in accordance with our present data regarding increased lipid content under 0.5 mg/L JA induction and decreased lipid production under 10-20.0 mg/ L JA induction in Chlorella strains. Furthermore, both SA and MJ at 500 mM concentrations displayed inhibitory effects on the growth of algal cells and carotenoid and chlorophyll contents, whereas higher concentrations of SA and MJ inhibited astaxanthin accumulation in Haematococcus pluvialis (Raman and Ravi, 2011). Gao et al (2012a) also reported that JA was an effective regulator that stimulated astaxanthin production in H. pluvialis.…”
Section: Discussionmentioning
confidence: 95%
“…The key role of phytohormones, such as ABA, JA, and SA, as critical components of complex signaling networks and primary signals involved in the defensive responses against various stresses has been well established, and compelling evidence demonstrates that these hormones are the primary signals inducing defense responses through recognized defense hormone signaling pathways (Bari and Jones, 2009;Raman and Ravi, 2011). These hormones generate a signal transduction network that leads to a cascade of events responsible for the physiological adaptation of the plant to stresses (Aimar et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…1,27 Our results are in accordance with the earlier reports where exogenous application of SA induced H 2 O 2 content in plants. 26,28 In addition, the ROS produced on SA treatment mediates the accumulation of cytosolic calcium that in turn triggers additional physiological processes. 29 Proteins play an important role in plant defense in the form of various defense enzymes and other protein based non enzymatic compounds.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Plant hormones such as salicylic acid (SA) and jasmonic acid (JA) are important components in the defense networks of plants and are involved in various functions in plant development. These hormones are reported to be present in both macro-and microalgae but the mechanism of action and metabolism of these hormones have not been studied thoroughly (Raman & Ravi, 2011). So far, studies have been limited to the effects of SA and methyl jasmonate (MJ) on growth and biochemical activity (Chlorella vulgaris; Czerpak et al 2002Czerpak et al , 2006, response to osmotic shock (Scenedesmus Fedina & Benderliev 2000), and astaxanthin and other carotenoid accumulation in Haematococcus pluvialis (Lu et al, 2010;Raman & Ravi, 2011;Gao et al, 2012a,b).…”
Section: Resultsmentioning
confidence: 99%
“…So far, studies have been limited to the effects of SA and methyl jasmonate (MJ) on growth and biochemical activity (Chlorella vulgaris; Czerpak et al 2002Czerpak et al , 2006, response to osmotic shock (Scenedesmus Fedina & Benderliev 2000), and astaxanthin and other carotenoid accumulation in Haematococcus pluvialis (Lu et al, 2010;Raman & Ravi, 2011;Gao et al, 2012a,b). Moreover, some of the carotenoid genes involved in astaxanthin production and the antioxidant enzymes in H. pluvialis have also been studied (Lu et al, 2010;Raman & Ravi, 2011;Gao et al, 2012a,b) in attempts to understand the mechanism of action of the hormones in this alga.…”
Section: Resultsmentioning
confidence: 99%